Determination of size and refractive index of single gold nanoparticles using an optofluidic chip - Y. Z. Shi (AIP Advances, 2017)
We report a real-time method to determine the size, i.e. diameter, and refractive index of single gold nanoparticles using an optofluidic chip, which consists of a quasi-Bessel beam optical chromatography. The tightly focused (∼ 0.5 μm) quasi-Bessel beam with low divergence (NA ∼ 0.04) was used to trap sub-100 nm gold nanoparticles within a long trapping distance of 140 μm. In the experiment, 60 to 100 nm gold nanoparticles were separated efficiently with at least 18 μm. The diameter and refractive index (real and imaginary) of single gold nanoparticles were measured at high resolutions with respect to the trapping distance, i.e. 0.36 nm/μm, 0.003/μm and 0.0016/μm, respectively.